An Examination of Spinoza’s Moral Philosophy - Esikot, Idorenyin F.; Bessong, Peter K; Ette, Emmanuel E. (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2019)
Spinoza’s moral philosopher represents his most concerted attempt to come to terms with the great philosophical questions of the existence and identity of God, the nature and origin of the human mind concerning God, the origin and nature of emotions, the power of emotions as they restrict freedom of choice. His ethics is derived from his metaphysics and psychology. His belief that everything emanates from a perfect and infinite God made him conclude that evil does not exist. Further, he argues that anything that happens could have happened otherwise since it emanated from the unchangeable laws of nature. The surest part of happiness according to Spinoza is the study of philosophy and meditation. Arising from the foregoing, this discourse views Spinoza’s doctrine as running contrary to human nature. For maintaining that everything is fated and determined including human disposition implies that all human actions can, therefore, be said to be amoral. The corollary of the above is that institutions such as law court, police, prisons, and judiciary, Christianity and Islam are superfluous, irrational and serving no purpose. Consequently, his postulates smack of a moral lacuna.